Risk factors and outcomes of gastrointestinal bleeding in patients with stable coronary artery disease: data from the observational registry of long-term antithrombotic therapy REGATTA-1 - A. L. Komarov; O. O. Shakhmatova; V. V. Korobkova; E. S. Novikova; E. V. Guskova; E. B. Yarovaya; T. V. Balachonova; A. G. Shuleshova; E. P. Panchenko (Российский кардиологический журнал)
Aim. To optimize the upper gastrointestinal bleeding (UGIB) risk scale in patients Material and methods. The UGIB risk scale was developed based on the with chronic coronary artery disease (CAD) receiving long-term antiplatelet therapy. prospective REGistry of long-term AnTithrombotic TherApy-1 REGATTA-1(ClinicalTrials.gov Identifier: NCT04347200). The registry includes 934 patients with stable CAD (men, 78,6%; median age, 61±10,7 years), 76% of whom were included after elective percutaneous coronary interventions and received dual antiplatelet therapy for 6-12 months. After a UGIB episode, patients were prescribed proton pump inhibitors. The 2015 European Society of Cardiology (ESC) scale was used for assessing the UGIB risk. In addition, we evaluated the ultrasound data on atherosclerotic burden (abdominal aorta and peripheral arteries).Results. The median follow-up was 2,5 years [1,1-14,7 years]. The incidence of UGIB was 1,9 cases per 100 patient/years. Recurrent UGIB episodes and thrombosis was recorded in 13,7% and 31,4%, respectively. Based on the results of a multivariate logistic regression, a novel scale for assessing the UGIB risk (REGATTA) has been developed. In accordance with the odds ratio, points were assigned for each independent risk factor (RF): age ≥80 years — 3 points, prior gastric erosion, peptic ulcer disease or UGIB — 3 points for each RF, anticoagulation therapy — 4 points, non-steroidal antiinflammatory drug therapy — 2 points. The atherosclerotic burden (peripheral atherosclerosis and/or abdominal aortic aneurysm; 2 points) and heart failure (in most cases after a myocardial infarction; 2 points) were marked as a new independent predictor. The cutoff value (≥4 points) was determined, reflecting the high UGIB risk (sensitivity, 80,4%; specificity, 84,5%). The REGATTA scale was more powerful than the traditional 2015 ESC scale: AUC of 0,88, (95% confidence interval, 0,86-0,9) vs AUC of 0,79, (95% confidence interval, 0,760,82) (p=0,04).Conclusion. The identified UGIB predictors (atherosclerotic burden and heart failure) and the developed REGATTA scale made it possible to improve the prognosis and prevention of UGIB in patients with stable CAD receiving long-term antiplatelet therapy.